Pengembangan EduKependudukan digital di sekolah siaga kependudukan untuk mewujudkan sustainable development goals (SDGs) - Endah Septiani; Dewi Liesnoor Setyowati; Hamdan Tri Atmaja (JINoP (Jurnal Inovasi Pembelajaran), 2022)
The research background dealt with the increased of estimated population of Indonesia which is currently anticipated by the Sustainable Development Goals (SDG). One of the actions to anticipate the population growth is through population education in schools, targeting youth who are candidates for the next generation and at the same time a component of development. The purpose of this research is to develop Edukependudukan digital or digital population education in realizing quality education in schools as an effort to achieve the Sustainable Development Goals (SDGs). Considering that the target of population education is the younger generation who need to follow the development of their age characteristics, it is necessary to have a technology-based model of population education. The stages of the method in this study used seven Research and Development steps from Borg and Gall. The results of the study show that the EduKependudukan digital scheme that has been developed into an implemented digital application in schools was showing valid, feasible and useful result for students. The results of the response test showed that the students' response to the application content was 83.13% in the good category and the student's response to the application design was 86.83 in the very good category. The results of the study showed that there was an increase in students' knowledge after using EduKependudukan digital as seen from the average score during the pre-test, which increased from 45.39 to 71.65 during the post-test. EduKependudukan digital can be used as a media for socializing population for high school students as an effort to realize quality education as Sustainable Development Goal 4 (SDG).